Human Phase Response Curves to Three Days of Daily Melatonin: 0.5 mg Versus 3.0 mg - Burgess, Helen J. (The Endocrine Society, 2010)
Context: Phase response curves (PRCs) to melatonin exist, but none compare different doses of melatonin using the same protocol. Objective: The aim was to generate a PRC to 0.5 mg of oral melatonin and compare it to our previously published 3.0 mg PRC generated using the same protocol. Design and Setting: The study included two 5-d sessions in the laboratory, each preceded by 7–9 d of fixed sleep times. Each session started and ended with a phase assessment to measure the dim light melatonin onset (DLMO). In between were 3 d in an ultradian dim light (<150 lux)/dark cycle (light:dark, 2.5:1.5). Participants: Healthy adults (16 men, 18 women) between the ages of 18 and 42 yr participated in the study. Interventions: During the ultradian days of the laboratory sessions, each participant took one pill per day at the same clock time (0.5 mg melatonin or placebo, double blind, counterbalanced). Main Outcome Measure: Phase shifts to melatonin were derived by subtracting the phase shift to placebo. A PRC with time of pill administration relative to baseline DLMO and a PRC relative to midpoint of home sleep were generated. Results: Maximum advances occurred when 0.5 mg melatonin was taken in the afternoon, 2–4 h before the DLMO, or 9–11 h before sleep midpoint. The time for maximum phase delays was not as distinct, but a fitted curve peaked soon after wake time. Conclusions: The optimal administration time for advances and delays is later for the lower dose of melatonin. When each dose of melatonin is given at its optimal time, both yield similarly sized advances and delays.